DOES HALAL TOURISM SUSTAINABLE? A NARRATIVE LITERATURE REVIEW - Suherlan, ADE (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This narrative literature review explores the sustainability of halal tourism. Halal tourism refers to travel and hospitality services that comply with Islamic principles and cater to the needs of Muslim travellers. The study examines various scholarly articles and research papers to assess the extent to which halal tourism aligns with sustainable practices. The review analyses halal tourism's environmental, socio-cultural, and economic aspects and its impact on destinations and communities. As many as 34 refereed academic journals and proceedings in halal tourism were chosen for analysis, presented in Table 1. In total, 71 articles published between 2014 and 2023 were examined. The findings of this review shed light on the potential challenges and opportunities for integrating sustainable practices within the context of halal tourism. This research contributes to a better understanding the relationship between halal tourism and sustainability and provides insights for industry stakeholders, policymakers, and researchers.